Pollutant Monitoring System for Mushroom Factory Liquid Waste using Arduino with 4 Sensor Integration - Sigitta H., Rito Cipta; Mubarok, Rizky; Rakhman, Arif; Prastyo, Firman Ardy; Prastyono, Rizki Noor; Arsiandro, Fadly Haris (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2026)
Mushroom production requires a specially designed medium for mushroom growth. Factory-scale composting methods utilize several media, which involve water to maintain moisture and chemical/organic fertilizers. The water used for mushroom cultivation contains hazardous substances, which, if dissolved and flowing into sewers, water sources, or community irrigation, can cause several problems, resulting in liquid pollutants. The purpose and main contribution of this research is to develop and implement pollutant monitoring system in mushroom factory liquid waste based on Arduino with the integration of four sensor parameters. The 4D method used includes the stages of define, design, develop, and disseminate. The goal is to develop pollutant monitoring system using four sensors. The feasibility analysis results have a percentage above 80% in the good category and are suitable for use. Accuracy analysis results are >80% in the good category. Temperature and pH also tend to be stable without significant changes. The pH value tends to be stable in the neutral range of 7.2–7.3, which is generally still suitable for supporting the survival of aquatic organisms. The dissolved oxygen (DO) levels in water are generally low, in the range of 2.46 to 3.01 mg/L, which is already below the standard for good water quality (generally >5 mg/L). Meanwhile, the turbidity parameter indicates pollution, marked by very high turbidity reaching 300 NTU. Then it shows a drastic decrease from very high conditions at the beginning of 300 NTU to approaching zero after further distance, indicating an effective natural sedimentation process in improving water clarity.